Spatial variation in species‐specific catch and size structures across a large‐scale and diffuse freshwater recreational‐only fishery. (22nd August 2021) - Ochwada‐Doyle, Faith; Miles, Nathan; Stark, Kate; Hughes, Julian; Murphy, Jeffrey; Lowry, Michael; West, Laurie
Abstract: In areas where commercial fishing is prohibited, demographic metrics obtained from recreational fisheries and fishery‐independent methods can be integral to population ecology and management. For Australian bass Percalates novemaculeata (Steindachner) and Murray cod Maccullochella peelii peelii (Mitchell), two key finfish species native to the recreational‐only fresh waters of New South Wales (NSW), Australia, recreational fishing surveys were combined with electrofishing methods to capture information on spatial patterns of exploitation and variation in size. The species' catch across NSW fresh waters (2013–2014) was estimated using a telephone‐diary longitudinal panel survey and examined for spatial effects using generalised linear mixed effects models. Length data, collected through electrofishing (2013–2015), were compared among geographic zones using Kolmogorov–Smirnov tests and kernel density estimate tests. Catch patterns for each species were mainly spatially static, but significant regional differences in the size composition of both species were detected. The findings are discussed in the context of current catch‐and‐release practices for Australian bass and the application of size limits for Murray cod to illustrate the value of quantitative spatial information from recreational surveys and fishery‐independent methods in developing evidence‐based management and conservation initiatives.